Acid and enzyme hydrolysis to convert pretreated areca nut (areca catechu l.) husk into glucose for bioethanol production by yeasts and Zymomonas mobilis NCIM 2915 - K J, Naveen Kumar; Thippeswamy, B; Krishnappa, M (Research in Biotechnology, 2015)
Production of renewable fuels, especially bio-ethanol from lignocellulosic biomass, holds remarkable potential to meet the current energy demand as well as to mitigate greenhouse gas emissions for a sustainable environment. Determining optimal pretreatment techniques for fermentation is essential for the success of lignocellulosic energy production process. The study involved the acid pretreatment and use of laccase enzyme to degrade the complex lignocellulosic biomass to simple sugars. Sugars so formed in turn are converted to ethanol by employing suitable yeast strains and bacterium Zymomonas mobilis. Different fermentation process like separate hydrolysis and fermentation process (SHF) and simultaneous saccharification and fermentation process (SSF) have been evaluated for the biethanol production. In separate hydrolysis and fermentation process, the higher ethanol production was in Zymomonas mobilis (44.97±3.21 g/L) and Schizosaccharomyces pombe (42.60±3.0 g/L), average ethanol production in Saccharomyces cerevisiae (33.13±1.96 g/L) and very low ethanol production in Candida shehatae (25.24±2.30 g/L). In simultaneous saccharification and fermentation process, the higher ethanol production was in Zymomonas mobilis (47.34±3.22 g/L) and Saccharomyces uvarum (44.18±2.67 g/L), average ethanol production in Pichia stipitis (34.71±1.89 g/L), and very low ethanol production in Saccharomyces cerevisiae (26.82±2.63 g/L) was monitored after the fermentation process. Structural changes of areca nut husk before and after acid pretreatment were further investigated through Scanning electron microscopy (SEM) and Fourier transformed infrared spectroscopy (FTIR). Hence, acid and enzymatic pre-treatment is more effective for ethanol production. Areca nut husk was revealed as a suitable substrate for ethanol production.